A Conceptual Study Of Entrepreneurial Intentions Based On The Theory Of Planned Behavior, Entrepreneurial Event Model And Theory Of Self-Efficacy - Ali, Muazam; Omar, Siti Sarah; Hasan, Nawzad Majeed (Res Militaris, 2023)
Purpose The Main Objective Of The Study Is To Explore Theoretical Relationships Among Various Entrepreneurial Intentional Theories On The Entrepreneurial Intention Of The University Students Of Gilgit-Baltistan. Methodology Basically, It Is A Conceptual Research Paper. This Paper Critically Reviewed Various Models Of Entrepreneurial Intention Such As, Self-Efficacy Theory, Entrepreneurial Event Model And Theory Of Planned Behavior (Tpb) Extensively. Results The Literature Reveals That Students’ Entrepreneurial Intention Can Be Predicated By Applying The Mentioned Theories And Model. It Further Validated That Tpb Has More Predictive Power As Compared To The Other Theories. Implications This Conceptual Research Paper Provides Some Meaningful Insight About The Factor Of Entrepreneurial Intention. It Facilitates And Provides Guidelines For The Government And Policy Makers In Studying Intention Of The University Students. Originality/Value It Is One Of The Comprehensive Studies Of Entrepreneurial Intention Mainly Focusing On The Rural Area’s University Students. Hence, This Research Study Provides A Valuable Contribution In The Literature Of Rural Entrepreneurial Intentions.